The Buddha of suburbia - Kureishi, Hanif (London : Faber and Faber, 2009)
Karim Amir life in suburban London with his English mother and Indian father is turned upside down when his father becomes the Buddha of Suburbia and falls in love with one of his disciples.
Adult.
Adult
Keywords: Boys -- Fiction; East Indians -- England -- Fiction; Fathers and sons -- Fiction; Bildungsromans; Boys -- Fiction; Domestic fiction; Father-son relationship -- Fiction; Indians -- Fiction; London (England) -- Fiction; London (England) -- Fiction; Bildungsromans; Domestic fiction